Tau Taa Wana Bulang Community’s Local Forest Conservation Culture - Sahlan, Sahlan; Ayyub, Rusli; K., Armin (Komunitas, 2023)
This study was conducted through a quantitative and qualitative method in three regions of Central Sulawesi: Tojo Una-Una, Banggai, and Morowali. The informants of this study were Forestry Governmental Agency and Office for Natural Resources Conservation Central Sulawesi Province, the traditional assembly of Central Sulawesi, Environmental activists (Walhi, PuGAR, FFI), Traditional Community activists (JKMA, AMAN, YRBI), head of sub-district, head of adat community, and some local figures. It is obtained that the local community of Tau Taa Wana Bulang has local wisdom that puts forward the principles of natural balance and forest preservation, which can encourage residents to be involved, individually and collectively, in preserving the community’s forests in the vicinity. The factors were analyzed by Wana community’s local wisdom (R2=0.92). The strategy of participative policy developed by the community of Wana was the improvement of the religious system, local tradition, and the socialization of traditional obedience, sacred areas, and other collective activities. The practice of cultural anticipation has resulted from forest preservation according to seven indicators: eternal forest preservation; control of forest destruction; permanently controlled forest; protection of forest area; diversity of Flora-Fauna; protection of biota a-biota ecosystem; and collective tradition conservation management unit.